Contribution of fishermans wives to increasing household income in Muara Telake village - Fitriyana Fitriyana; Etik Sulistiowati Ningsih; Yulianti Yulianti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The contribution of fishermen's wife to fishermen's household income in Muara Telake Village is a description or role of women's position in household economic activities. The research was conducted in Muara Telake Village with 40 household respondents using apurposive sampling method. The research data were analyzed using the method of business cost analysis to generate profits and analysis of the contribution of fishermen's wife to determine how much the contribution of fishermen's wife to the income of fishermen's households. The results showed that the activities of fishermen's wife consisted of salted fish processors and fish or shrimp crackers producers. Fishermen's household income reached 183.939.458,33 IDR/month with an average of 4.598.486,46 IDR/month/respondent. The largest contribution to fishermen's family income comes from the head of the household, namely the husband, amounting to 3.408.135,42 IDR/month or with a percentage value of 74.11%. The contribution of fishermen's wife in increasing household income is included in the medium category, which can provide additional income of 1.190.351,04 IDR/month with a percentage value of 25.89%.Keywords:Financial AnalysisEconomic ContributionFisheries Sector